Եկեղեցական միության գաղափարը Ներսես Շնորհալու պատմափիլիսոփայական դավանանքի մեջ - Միրումյան, Ռիմա (Լիմուշ հրատ.)
The article postulates and substantiates the thesis that the idea of uniting churches fits into one of the levels of the universal problem of the philosophy of history - the antinomy “state-society”, and the question “state-church” (politicsreligion). At a deep level, the problem is perceived as a clash between the secular and spiritual principles in the life of a nation/nations, and ultimately, between cosmopolitan and national cultural systems. Divided after the Council of Chalcedon, the Christian Church for centuries was focused on disputes over confessional and ritual issues. Due to certain political circumstances in the 12th century, the Christian world faced the issue of uniting churches, which was understood as the unification of all churches under the “protectorate” of the Roman or Byzantine Church. Nerses Shnorhali changed the semantic content of the idea of unification: the issue of church policy was not the unification of churches, but their mutual understanding and the establishment of friendly relations between them.
Keywords: Եկեղեցական քաղաքականություն; Փիլիսոփայություն